2014
DOI: 10.1155/2014/372738
|View full text |Cite
|
Sign up to set email alerts
|

Interfractional Variations of Tumor Centroid Position and Tumor Regression during Stereotactic Body Radiotherapy for Lung Tumor

Abstract: Purpose. To determine interfractional changes of lung tumor centroid position and tumor regression during stereotactic body radiation therapy (SBRT). Methods and Materials. 34 patients were treated by SBRT in 4-5 fractions to a median dose of 50 Gy. The CT scans acquired for verification were registered with simulation CT scans. The gross target volume (GTV) was contoured on all verification CT scans and compared to the initial GTV in treatment plan system. Results. The mean (±standard deviation, SD) three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous studies found that the mean GTV reduction was about 19–51.1% in patients treated by conventional fractionated radiotherapy [ 22 25 ]. A less marked reduction in tumor volume was obtained during SBRT due to the short irradiation course, with the mean GTV reduction of 12.8–32% [ 26 , 27 ]. In current study, we detected a gradual shrinking of tumor volume over the course of treatment with median reduction of 11.1%, which suggested only a fraction of patients could benefit from ART.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the mean GTV reduction was about 19–51.1% in patients treated by conventional fractionated radiotherapy [ 22 25 ]. A less marked reduction in tumor volume was obtained during SBRT due to the short irradiation course, with the mean GTV reduction of 12.8–32% [ 26 , 27 ]. In current study, we detected a gradual shrinking of tumor volume over the course of treatment with median reduction of 11.1%, which suggested only a fraction of patients could benefit from ART.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the mean GTV reduction was about 19%-51.1% in patients treated by conventional fractionated radiotherapy [22][23][24][25]. A less marked reduction in tumor volume was obtained during SBRT due to the short irradiation course, with the mean GTV reduction of 12.8%-32% [26,27]. In current study, we detected a gradual shrinking of tumor volume over the course of treatment with median reduction of 11.1%, which suggested only a fraction of patients could bene t from ART.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, although lower fetuin-A levels were associated with greater CVD risk in nondiabetic people, in diabetic people, the opposite trend was observed [ 36 ]. Finally, a recent meta-analysis of 10 case-control studies including over 1200 patients with cardiovascular disease and 2600 healthy controls concluded that lower serum fetuin-A levels correlated with the development of cardiovascular disease [ 37 ]. Additional evidence suggests that there may be a sex-specific relationship between fetuin-A, VO 2max , and coronary artery calcification.…”
Section: Discussionmentioning
confidence: 99%